CITRA TUBUH, ASUPAN MAKAN DAN STATUS GIZI WANITA USIA SUBUR (WUS) PRANIKAH DI KOTA YOGYAKARTA - , Yhona Paratmmitya, Prof. dr. Hamam Hadi, MS,Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background : Premarital women of reproductive age is a prospective mother that should be noticed for their nutritional status, because it can affect their pregnancy outcome. Premarital period can be interpreted as pre conception period. As the wedding ceremony approach, concern of their body image is increasing. Negative body image can influence their dietary intake and their nutritional status. Research about the effect of pre-wedding body image on womenâs dietary intake and nutritional status in non-western countries is still limited. Objective : The aim of this research was for describing the relationship between body image, dietary intake and nutritional status of premarital women of reproductive age in Yogyakarta city. Design : This research was an observational research with cross-sectional design. Method : Study was carried out on premarital women of reproductive age in Yogyakarta city who came to the religious affairs office to registered their marriage or followed the premarital advisory. The number of participant were 157 women. Body image was measured with Body Shape Questionnaire (BSQ-34), dietary intake was measured with Semi-Quantitative Food Frequency Questionnaire (SQFFQ), and nutritional status was classified based on Body Mass Index (BMI). Data were analyzed with Chi-Square test, t-test, and multiple logistic regression analysis. Result : Only 12,1% of participant who claimed their body image dissatisfaction. Dominant factor that influence their body image was environmental influence (OR = 14,5). The results of bivariat analysis showed the relationship of body image and nutritional status (p<0,05